Side effect of acting on the world: acquisition of action-outcome statistic relation alters visual interpretation of action outcome - Kawabe, Takahiro (Frontiers in Human Neuroscience, 2013)
Humans can acquire the statistical features of the external world and employ them to control behaviors. Some external events occur in harmony with an agent’s action, and thus humans should also be able to acquire the statistical features between an action and its external outcome. We report that the acquired action-outcome statistical features alter the visual appearance of the action outcome. Pressing either of two assigned keys triggered visual motion whose direction was statistically biased either upward or downward, and observers judged the stimulus motion direction. Points of subjective equality (PSE) for judging motion direction were shifted repulsively from the mean of the distribution associated with each key. Our Bayesian model accounted for the PSE shifts, indicating the optimal acquisition of the action-effect statistical relation. The PSE shifts were moderately attenuated when the action-outcome contingency was reduced. The Bayesian model again accounted for the attenuated PSE shifts. On the other hand, when the action-outcome contiguity was greatly reduced, the PSE shifts were greatly attenuated, and however, the Bayesian model could not accounted for the shifts. The results indicate that visual appearance can be modified by prediction based on the optimal acquisition of action-effect causal relation.